Toward a better understanding of microalgal photosynthesis in medium polluted with microplastics: a study of the radiative properties of microplastic particles - Yang, Limin; Ma, Chunyang (Frontiers in Bioengineering and Biotechnology, 2023)
Due to the wide presence of microplastics in water, interaction between microplastic particles and microalgae cells in medium merits the attentions of researchers. Microplastic particles can impact the original transmission of light radiation in water bodies since the refractive index of microplastics is different from that of water bodies. Accordingly, the accumulation of microplastics in water bodies will certainly impact the microalgal photosynthesis. Therefore, experimental measurements and theoretical studies as characterizing the radiative properties of the interaction between light and microplastic particles are highly significant. The extinction and absorption coefficient/cross-section of polyethylene terephthalate and polypropylene were experimentally measured using transmission and integrating methods in the spectral range 200 to 1100 nm. The absorption cross-section of PET shows remarkable absorption peaks in the vicinity of 326 nm, 700 nm, 711 nm, 767 nm, 823 nm, 913 nm, and 1046 nm. The absorption cross-section of PP has distinctive absorption peaks near 334 nm, 703 nm, and 1016 nm. The measured scattering albedo of the microplastic particles is above 0.7, indicating that both microplastics are scattering dominant media. Based on the results of this work, an in-depth understanding of the interaction between microalgal photosynthesis and microplastic particles in medium will be obtained.